Multiple Role of Women Workers In Institution of Social Security Employment - Roziana Ainul Hidayati; Siti Aisyah (INNOVATION RESEARCH JOURNAL, 2021)
Nowadays the existence of women in the world of work is increasing. The phenomenon of women to have a dual role can not be damned. The tendency of women to work raises problems. When working women are faced with the demands of work, while when they are at home women will be faced with domestic roles. In this case working mothers can have different performance. The purpose of this study is to analyze how the quality of the performance of women workers who have a dual role in the BPJS Employment Gresik office. The method used in this study is qualitative. Informants in this study are mothers who have multiple roles who have 9 children. Based on the results of research and discussion on the quality of performance of women workers who have multiple roles, the researchers came to the conclusion that women workers who have multiple roles still carry out their work well so as to achieve optimal performance